APLIKASI SISTEM INFERENSI FUZZY UNTUK MENDIAGNOSIS PENYAKIT MATA BERBASIS WEBSITE - Fabrian Ivan Prasetya; Chairisni Lubis (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
On this research a fuzzy inference system application program will be designed to diagnose web-based diseases. In addition to diagnosing the disease, this research was conducted to increase the severity of the disease. Data collection in this study uses the literature method, documentation method, and interview method. The inference engine used is the forward chaining method and the calculation of the severity using the Sugeno’s fuzzy method with triangular and trapezoidal membership functions. Fuzzy Inference System Application Program created can be used to diagnose diseases in general that can contain various types of diseases, symptoms, rule bases and diagnosis results of a disease and its symptoms based on the symptoms of the disease suffered. In this study, the application was created by using ASP.NET and SQL Server 2019. Data testing was carried out there were two types of testing. The results of the percentage of truth in diagnosing the severity of the disease reached 92.30% and in diagnosing the disease using the triangle function reached 52.56% in the first test and by using the trapezoidal function reached 53.84% in the first test. For the second test result, the percentage of truth in diagnosing the severity of the disease was 89.65% and in diagnosing the disease using the triangle function reached 41.37% and by using the trapezoidal function reached 41.37%